Analysis on structural pattern of plotline and myths in Malaysian folktales - Jasmine Serinie, Martin (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study focused on the plot construction and the significance of myths in Malaysian folktales. The aims of this study are to investigate the structural pattern of Malaysian folktales plotline based Propp’s thirty-one function and Levi-Strauss studies on myths based on structuralism theoretical framework. Fifty Malaysian folktales were selected from 366 A Collections of Malaysian Folktales which was compiled by Othman Puteh and Arripin Said and used for this study. The fifty folktales were analysed based on Propp thirty-one functions with the plotline of the texts and the significance of myths were analysed based on Levi-Strauss’s studies on myth. Based on the research conducted, Malaysian folktales did not confirmed to Propp’s thirty-one functions but shared a similar pattern of five stages of plotting which were exposition, rising action, climax, falling action and resolution. The significance of myths in Malaysian folktales were viewed as allegorical, had its aesthetic value, moral education and explanation of nature phenomenon.